Canonical variables in MHD flows with shocks and other breaks - Kats, A.V.; Korabel, V.N. (Вопросы атомной науки и техники, 2000)
The rigorous method of introduction of hamiltonian variables in MHD flows with discontinuities is presented. Appropriate boundary conditions are obtained and proved to give conventional continuity conditions at the boundary.